WPŁYW BEZDZIETNOŚCI NA STOSUNKI W MAŁŻEŃSTWIE - Przybył, Iwona (Wydział Prawa i Administracji UAM, 2002)
The aim of the article is to analyse the influence o f childlessness, in particular resulting from infertility, upon the scope of the partners’ co-operation and the self-appraisal of the marriage. The analysis has been carried out on the basis of relevant literature in addition to the author’s own research. The first part of the article includes an overview of the results of psycho- and sociological research on the mental and social results of infertility in a marriage. Although infertility heavily affects the emotional and sexual life o f a couple, it is difficult to ascertain to what extent this factor generates a marital crisis. The second part discusses the results of research done by the author on 140 voluntarily and involuntarily childless marriages. The co-operation intensification factor, proposed by the author, allows to distinguish three types of married couples: not co-operating, moderately co-operating, and strongly co-operating between one another. The results of the research show that the type of childlessness (voluntary or not, temporary or permanent) is related neither to the intensity of co-operation nor to the appraisal of the relationship by the couple itself. By contrast, it is rather the duration of time spent together in the marriage that does influence both the co-operation intensity and self-appraisal. The longer the marriage lasts, the less childless partners are likely to co-operate and consider their marriage happy.
THE INFLUENCE OF CHILDLESSNESS UPON THE RELATIONSHIPS WITHIN A FAMILY